Catchpenny : a novel - Huston, Charlie (Vintage Books, 2024)
"A thief who can travel through mirrors, a video game that threatens to spill out of the virtual world, a doomsday cult on a collision course with destiny, and a missing teenager at the center of it all. With the world on the brink of every kind of apocalypse, humanity needs a hero. What it gets is Sid Catchpenny. Sidney Catchpenny has had a bad run. Laid low by a years-long bout of debilitating depression, he's all but squandered his reputation as one of the most uniquely talented thieves in LA. There aren't many who can do what Sid does. He's a sly, a special kind of crook with the uncanny ability to move through mirrors. And the spoils he's after are equally unusual. Forget jewels and cold cash--Sid steals curiosities-items imbued with powerful mojo, a magical essence gleaned from the accumulated emotion that seeps into interesting, though often banal objects. That spot on the carpet where your old dog used to lay at your feet? The passed-down family heirloom nobody wants but everybody refuses to throw away? These curiosities are full of mojo, which is both the currency of the criminal underground and the secret source of magic in the world. When a friend from Sid's past comes looking for his help with an important client, and the chance to pay off old debts presents itself, Sid seizes the opportunity ... as best he can. But the case he stumbles into is more complicated than it seems, and it portends a seismic shift in the world, one that will leave no one untouched. As the fog of his depression begins to lift, Sid sees connections everywhere he looks, and the once disparate threads of the case--a missing teenage girl, an entire bedroom saturated with mojo, and Sid's own long-dead wife--begin to coalesce"--